THE EFFECT OF SHARIA RELATIONSHIP MARKETING ON CUSTOMER LOYALTY AT BANK BSI MAKASSAR WITH SATISFACTION OF INTERVENING VARIABLES - Trimulato, Trimulato; Mustamin, Arsyaf; Syarifuddin, Syarifuddin (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2025)
This research influences characteristics Sharia marketing and Sharia relationship marketing on customer loyalty at BSI KCP Makassar. Analyze the effect of Sharia marketing and relationship marketing characteristics loyalty with customer satisfaction as an intervening variable. A research method is quantitative. The primary data source is primary data, distributed directly through questionnaires. Secondary data has been presented from various sources. The data collection technique used a questionnaire (questionnaire) with a sample of 67 respondents and literature from several relevant sources. The research data analysis technique is path analysis with reliability tests, validity tests, and classical assumption tests including multicollinearity, heteroscedasticity, normality, and linearity tests. Hypothesis testing includes testing coefficient determination, T-test, and F-test. Results showed characteristics Islamic marketing had a significant positive effect on customer loyalty, BSI Makassar, with a Tcount 2,210 > Ttable 1.997 and a significance value 0.031 at an alpha coefficient of 5%. Sharia relationship marketing has a significant positive effect on customer loyalty at BSI Makassar with a T-count 3,475 > Ttable 1.997 and a significance value 0.031 with an alpha coefficient 5%. Characteristics of sharia marketing and relationship marketing have a significant positive effect on loyalty and customer satisfaction when using the intervening variable value Tcount=2.0412 greater than Ttable=1.99834.